Fundamentals of transfer pricing general topics and specific transactions - Petruzzi, Raffaele, 1983-; Cotani, Giammarco; Lang, Michael, 1965- (Wolters Kluwer Law International, 2021)
Transfer pricing is one of the most relevant and challenging topics in international taxation. Over the last century, nearly every country in the world introduced transfer pricing rules into their domestic legislation. Indeed, it was estimated that profit shifting generated by the improper application of transfer pricing rules has resulted in global tax losses worth USD 500 billion for governments ? 20% of all corporate tax revenues. It is thus imperative that all tax professionals thoroughly understand the nature of transfer pricing and how the growing body of applicable rules works in practice. In this crucially significant volume, stakeholders from government, multinational companies, international organisations, advisory groups and academia offer deeply informed perspectives, both general and specific, on the practical application of transfer pricing rules, taking into consideration all the most recent developments.